(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
During last few years the banking service have been grown exponentially. Number of banks have been increased and the customer expectation have increased too. Researchers found a scope to study the service quality perception of the customers in State Bank of India. Researchers have conducted a survey of 480 customers to find out their opinion for service quality in SBI. The researchers have developed a questionnaire with 25 statement to measures different quality aspects of services. The findings suggested that customers are satisfied with SBI services.